The Influence Of Earning Management On Capital Structure Through Firm Size As An Intervening Variable In Sharia Commercial Banks: The Influence Of Earning Management On Capital Structure Through Firm Size As An Intervening Variable In Sharia Commercial Banks - Israeni, Israeni; Yudih, Sudirman; Mustamin, Asyraf (Jurnal Ilmiah Akuntansi Peradaban, 2024)
The study aims to analyze the impact of profit management on the capital structure through the size of the company as an intervening variable on the Sharia General Bank (BUS). The data used in this study is secondary data, with panel data models over nine years, from 2019 to 2023. The research data was analyzed using the path analysis method (path analysis) with the help of SMART-PLS software version 3. The results of the research showed that profit management had a positive and significant influence on the capital structure of the BUS, profit management has a positive influence and significant effect on the size of the company in the Sharial General Bank, company size did not have a significant impact on the structure of capital in BUS, and indirectly profit management did not influence the structures of capital through the company size at BUS.